EFEKTIVITAS PEMBELAJARAN DARING PADA ANAK KELOMPOK B UNTUK MENINGKATKAN KEMAMPUAN VISUAL SPASIAL DENGAN MENGGUNAKAN PENERAPAN SENI RUPA DUA DIMENSI - Santi Fitriani; Fifiet Dwi Tresna Santana (IKIP Siliwangi, 2023)
Online learning, especially in art learning for children, has not been effective in improving children's visual-spatial abilities. This is due to the lack of teachers in terms of scenarios and implementation of learning, teachers' lack of understanding of fine arts, and the development of visual-spatial abilities. So that in this problem there needs to be a solution to increase the effectiveness of online learning, one of which is done by developing children's art skills with two dimensions. This study uses a qualitative descriptive method to know the visual-spatial ability of children by using the application of two-dimensional art. The data collection techniques were carried out using observation, interviews, and documentation studies. While the data analysis technique is done by data reduction, data display, and verification. The results of this research are through learning activities of the application of two-dimensional art to improve children's visual-spatial that is effective in online learning through WhatsApp, as well as scenarios and implementation of learning carried out in a structured, planned, and gradual manner starting from the preparation of teaching materials, learning methods, learning media, and evaluation system by standard provisions. Student responses are generally positive, it can be seen from the development of children's art skills with two dimensions. The teacher's response is generally positive, it can be seen from the percentage of difficulties experienced by the teacher for each item below fifty percent. Pembelajaran daring terutama pada pembelajaran seni rupa pada anak dalam peningkatan kemampuan visual spasial anak belum efektif. Hal ini disebabkan kurangnya guru dalam hal skenario dan implementasi pembelajaran, kurangnya pemahaman guru tentang seni rupa dan pengembangan kemampuan visual spasial. Sehingga dalam permasalahan tersebut perlu adanya solusi untuk meningkatkan efektivitas pembelajaran daring salah satunya dilakukan dengan mengembangkan kemampuan seni rupa anak dengan dua dimensi. Penelitian ini menggunakan metode deskriptif kualitatif dengan tujuan untuk mengetahui kemampuan visual spasial anak dengan menggunakan penerapan seni rupa dua dimensi. Adapun teknik pengumpulan data dilakukan dengan cara observasi, wawancara, dan studi dokumentasi. Sedangkan teknik analisis data dilakukan dengan reduksi data, display data dan verifikasi. Adapun hasil penelitian ini melalui kegiatan pembelajaran penerapan seni rupa dua dimensi untuk meningkatkan visual spasial anak yakni efektif dalam pembelajaran daring melalui whatapp, serta skenario dan implementasi pembelajaran dilakukan secara terstruktur, berencana, dan bertahap dari mulai penyiapan bahan ajar, metode pembelajaran, media pembelajaran, dan sistem evaluasi sesuai dengan ketentuan baku. Respon siswa pada umumnya positif, hal itu dapat dilihat dari perkembangan kemampuan seni rupa anak dengan dua dimensi. Respon guru pada umumnya positif hal itu dapat dilihat dari persentase kesulitan-kesulitan yang dialami oleh guru setiap itemnya di bawah 50%.